Signaling pathways of nucleic acids for bone healing: A review - Camal Ruggieri, Iván Nadir (2020)
Different kinds of nucleic acid (NA) molecules are promising therapeutic tools in a variety of tissues and their pathogenesis, and bone pathologies are not the exception. NAs interact in cytosol or nucleus to generate a specific response. Some of these NAs can be used to generate a positive response in relation to bone formation and differentiation in osteoblast and osteocyte. This work aims to briefly and clearly show main signaling pathways in osteoblasts and osteocytes, and to state the mechanism of how miRNA agonists (miRNA) and miRNA antagonists (antagomir) affect them. Thus, this summarizes the mechanism of promising therapeutic strategies for bone repair. NAs are fragile and can be degraded quickly outside the cells. These problems are more and more frequently resolved by nanotechnology and tissue engineering approaches. Further research in this field wills probably generate safe and therapeutic effective therapy in relation to bone healing.